Análise renal de ultramaratonista em prova de 75 km - Lopes, Thiago Ribeiro [UNIFESP] (2009)
OBJECTIVE: To identify urinary abnormalities, indicative of renal involvement, in 75 km ultra-marathon racer and pacer (cyclist that gives support to the racer). METHODS: Renal analysis consisted of urine dipstick tests in four different times and anthropometric measures. RESULTS: Both the racer and the pacer were in eutrophic conditions. There was an association between the capacity for maximum physical effort and detection of urinary abnormalities determined by the presence of hematuria and/or proteinuria. CONCLUSION: Renal analysis allowed the identification of transitory renal involvement in both healthy individuals during intense exercise.